Feminist Counselling in Action. - Chaplin, Jocelyn (Counselling in Action series., 1999)
Praise for the First Edition: 'One of the best, and clearest, descriptions of the significance of the imposition of "masculine" patterns of thought on a culture ... a lucid and non-jargon-fraught account of the strands of thought which make up the feminist approach to and adaptation of psychotherapy' - The Guardian For counsellors, therapists, trainees and others who want a deeper understanding of how society affects them psychologically, the revised and updated edition of Feminist Counselling in Action is the ideal resource. Drawin.